Assessing quality of life and associated factors in post-stroke patients using the world health organization abbreviated generic quality of life questionnaire (WHOQOL-BREF) - Santi Martini; Defi Amalia Setia Ningrum; Khadizah H. Abdul-Mumin; Chung Yi-Li (Clinical Epidemiology and Global Health, 2022)
Introduction: This study piloted the World Health Organization Quality of Life short version form (WHOQOL-BREF) to compare the quality of life (QoL) in post-stroke patients who followed the medical stroke rehabilitation program and those whom did not. This study determined which quality of life domains were mostly affected by stroke, and whether there are influencing factors other than rehabilitation. Methods: A cross-sectional study was conducted at Public Hospital in Surabaya. Patients with stroke less than two years since the first attack were included in this study (n = 52). Cronbach's alpha test was performed to assess the internal consistency of WHOQOL-BREF questionnaire. The independent t-test and ANOVA were used to compare the differences between patient's characteristics and the six domains of QoL (i.e., perception of QoL, perception of health, physical of health, psychological health, social relationship, and environmental health). Multiple linear regression was performed to assess the influential factors of QoL. Results: post-stroke patients aged more than 50 years old (76.9%), male (55.8%). But, only 48.1% of those patients participating in medical rehabilitation programs. Age group was significantly associated with QoL in the psychological health domain (p = 0.021); participating in medical stroke rehabilitation programs was significantly associated with social relationship domain (p = 0.026) and the education level was significantly associated to physical health (p = 0.005), psychological heath (p = 0.035) and perception of health (p = 0.003). Conclusion: Lower education level was significantly associated with a low perception of health, one of QoL domains; and it was the most influential factor of QoL among post-stroke patients.